The importance of sport and recreational activities for children with disabilities: investigating parent’s perception - Samshudar, Siti Azizah (Universiti Sains Malaysia, 2015)
Participation in recreational and sport activity promotes social wellbeing, as well as physical and mental health. Recreational and sport activities provide learning opportunities for children such as learn skills for teamwork, self-discipline, sportsmanship, leadership, and socialization. All children would benefit from sport and recreational activities including children with disabilities. This is a study of parent's perception about participation in recreational and sport activities towards children with disabilities. It is an investigation on the importance of participation in recreational and sport activities for children with disabilities. 61 parents who have children with disabilities. All respondents completed the modified and translated questionnaire. In this study, descriptive statistics (such as means and frequencies) were used to explore trends in parent's perception of importance and factors of supports and barriers for the participation in recreational and sport activities towards children with disabilities.This study demonstrates that the majority of parents have good level of understanding of recreational and sport activity. This study also examined that majority of parents agreed recreational and sport activity is very important to children with disabilities. Majority of respondents agreed the factor of supporting and barriers in the encouragement of children with disabilities to participant in recreational and sport activities. The parents acknowledged the importance for children with disabilities to participate activities in recreational and sport activities. They also provided several of supporting and barriers that influence children participation in sport and recreational activities.